2020
DOI: 10.1016/j.jpeds.2020.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Health and Educational Outcomes After Neonatal Abstinence Syndrome: A Systematic Review and Meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…infants born preterm, multiple births, extremely low birthweight infants, and other risk factors) 16,18 . While most studies found higher rates of cognitive impairment and behavior problems and lower school/academic performance after IUDE, reports of motor outcomes after IUDE are limited 4,5,8,9,11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…infants born preterm, multiple births, extremely low birthweight infants, and other risk factors) 16,18 . While most studies found higher rates of cognitive impairment and behavior problems and lower school/academic performance after IUDE, reports of motor outcomes after IUDE are limited 4,5,8,9,11 …”
Section: Discussionmentioning
confidence: 99%
“…According to the 2019 National Survey on Drug Use and Health, 5.8% of pregnant females reported using illicit substances, 9.6% using tobacco products, and 9.5% drinking alcohol in the month before survey collection 1 . Substance use during pregnancy can have significant short‐ and long‐term health consequences for exposed infants 2–4 . With increasing evidence for the long‐term effects of intrauterine drug exposure (IUDE), developmental surveillance to improve trajectories is critical 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies suggest that POE, as a result of both illegally obtained and prescribed opioids, is associated with long-term adverse developmental outcomes. Results from four recent meta-analyses, summarizing over 50 studies, consistently demonstrate worse outcomes for children with POE (Andersen et al 2020;Lee et al 2020;Rees et al 2020;Yeoh et al 2019). Developmental domains affected include cognition, language, motor function, socio-emotional skills and visual deficiencies such as strabismus and nystagmus.…”
Section: Developmental Healthmentioning
confidence: 97%
“…Developmental domains affected include cognition, language, motor function, socio-emotional skills and visual deficiencies such as strabismus and nystagmus. For example, meta-analytic evidence examining the impact of POE (due to OAT or illegally obtained opioids) on cognitive outcomes concluded that children exposed to opioids prenatally are three times more likely to have a severe intellectual disability (Andersen et al 2020;Lee et al 2020;Rees et al 2020;Yeoh et al 2019). However, many studies had important limitations (e.g., small sample sizes, observational designs) and differences in study characteristics (e.g., type of opioid exposure, age of assessment), making it difficult to draw definitive conclusions about the direct effect of opioid exposure.…”
Section: Developmental Healthmentioning
confidence: 99%